Differential effects of pH on cadmium accumulation in Artemisia argyi growing in low and moderately cadmium-contaminated paddy soils - Ze Zhang; Jia-shun Zhong; Xin-zhi Guo; Chao Xu; Dao-you Huang; Jing Liu; Xin-sheng Chen (Chemical and Biological Technologies in Agriculture, 2024)
Abstract Background Phytoremediation is affected by physical and chemical properties of the soil such as soil pH, moisture, and nutrient content. Soil pH is a key element influencing Cd bioavailability and can be easily adjusted in agricultural practices. The soil pH level may relate to the effectiveness of phytoremediation; however, this has not been extensively investigated. In the current study, we evaluated the effect of Cd contamination level (0.56 and 0.92 mg/kg) and soil pH (5, 6, and 7) on Cd accumulation and allocation in Artemisia argyi, a fast-growing perennial crop. Results Our results indicated that higher soil Cd concentrations reduce A. argyi biomass, and the loss of the root mass was particularly significant. Higher soil pH decreased Cd content in stems and roots of A. argyi cultivated in moderately Cd-polluted soil, and increased Cd content in stems and roots of the plant grown in low Cd-polluted soil. Higher soil pH decreased the percentage of Cd distributed in the soluble fraction and cell walls and increased the percentage of Cd in the organelles of leaf cells for moderate soil Cd levels. The bioconcentration and translocation factor exceeded 4.0 and 1.0, respectively, across all tested treatments, indicating that A. argyi is a promising candidate for phytoremediation. Notably, the effects of soil pH on Cd accumulation and subcellular distribution in A. argyi differed between low and moderately Cd-contaminated soils. Conclusion Adjustments to soil pH based on the degree of Cd contamination can enhance Cd extraction by A. argyi, thereby reducing the overall remediation cycle of cadmium-polluted paddy fields of South China. Graphical Abstract